2019
DOI: 10.1111/jth.14589
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and functional limitations after pulmonary embolism and its prognostic relevance

Abstract: BackgroundWhile the importance of patients’ quality of life (QoL) in chronic cardiac or pulmonary disease is uncontroversial, the burden of an acute pulmonary embolism (PE) on QoL has received little attention thus far.ObjectivesWe aimed to validate the German PEmb‐QoL questionnaire, identify associations between QoL and clinical/functional parameters, and investigate the prognostic relevance of QoL for long‐term survival in survivors of an acute PE episode.Patients/MethodsPatients were invited for a clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 46 publications
4
33
0
2
Order By: Relevance
“…Venous thromboembolism (VTE) is a collective term encompassing deep vein thrombosis and pulmonary embolism and a well-known complication to orthopedic surgery affecting both short and long-term mortality and quality of life. [1][2][3] More than 700 000 Europeans develop a VTE each year, and another 370 000 deaths annually are attributed to VTE, with only a minor fraction of the patients being diagnosed with and treated for VTE antemortem. 4 More than 60% of all VTEs are associated with hospitalization and occur after discharge from the hospital.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous thromboembolism (VTE) is a collective term encompassing deep vein thrombosis and pulmonary embolism and a well-known complication to orthopedic surgery affecting both short and long-term mortality and quality of life. [1][2][3] More than 700 000 Europeans develop a VTE each year, and another 370 000 deaths annually are attributed to VTE, with only a minor fraction of the patients being diagnosed with and treated for VTE antemortem. 4 More than 60% of all VTEs are associated with hospitalization and occur after discharge from the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Orthopedic surgical procedures are some of the most commonly provided services in the health care systems worldwide. Venous thromboembolism (VTE) is a collective term encompassing deep vein thrombosis and pulmonary embolism and a well‐known complication to orthopedic surgery affecting both short and long‐term mortality and quality of life 1‐3 . More than 700 000 Europeans develop a VTE each year, and another 370 000 deaths annually are attributed to VTE, with only a minor fraction of the patients being diagnosed with and treated for VTE antemortem 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Our patient experienced some functional limitations and decreased quality of life with delayed PE diagnosis. She would have continued taking TXA without caution and could have been at risk of developing more serious PE complications, such as chronic thromboembolic pulmonary hypertension, life-threatening acute right (heart) ventricular failure, pulmonary infarction, and cardiac arrest, among other problems [ 22 24 ]. Worse still, this woman could have been sent home after the third hospital visit with a false reassurance that her symptoms were likely musculoskeletal pain following the absence of significant risk factors for PE.…”
Section: Discussionmentioning
confidence: 99%
“…Natural course of symptom recovery after acute PE Several cohort studies have shown that approximately 40-50% of patients reports persistent or worsening dyspnoea and functional limitations in the course of adequately treated acute PE, a prevalence of dyspnoea that is higher than expected in the general population and greatly affects quality of life. [15][16][17][18][19][20][21][22][23][24] In these studies, dyspnoea was defined as symptoms corresponding to a New York Heart Association (NYHA) functional class of ≥II, with 10-20% of patients categorized as NYHA functional class III or IV. [15][16][17][18] Notably, symptoms of dyspnoea and results of a 6-minute walking test 5 improve in the majority of patients in the first year months following an acute PE diagnosis, although most improvement occurs in the first three months.…”
Section: Who and When To Test For Cteph?mentioning
confidence: 99%